SISTEM PENGENDALIAN INTERN, TEKNOLOGI INFORMASI, SUMBER DAYA MANUSIA DAN KOMITMEN ORGANISASI TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH KOTA SEMARANG - Saifudin Saifudin; Rizki Nur Aprilia (Politeknik Negeri Malang, 2020)
This study aims to analyze the influence of internal control systems, information technology, human resources and organizational commitment to the quality of the Semarang City goverment’s financial statements . This type of research is a quantitative study using primary data. Data collection techniques through questionnaires. The population in this study OPD Semarang City. The sampling technique uses purposive sampling. The sample of this study were 80 respondents. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that (1) internal control system affect the quality of financial statements, (2) information technology affects he quality of financial statements, (3) human resources affect he quality of financial statements, (4) organizational commitment doesnt affect he quality of financial statements.